Encounters with the ineffable in selected artworks by Anish Kapoor and Karel Nel - Kalan, Sheekha (My University, 2016)
In this research I examine how the ineffable is addressed and explored in selected artworks by British-Indian artist Anish Kapoor (b 1954) and South African artist Karel Nel (b 1955). I introduce the notion of the ineffable, described as that which is too great or profound to be expressed in words; the ungraspable, indescribable, indefinable. It is often linked to the spiritual, the fluid and unfixed, the transcendent and the notion of the revelatory. I consider it alongside related terms such as the sublime, the numinous, the mystical etc. In examining how it can be seen to link to artists’ aesthetic pursuits, I briefly consider the idea of the shamanistic role of the artist in providing a ‘transformative event’ of bringing the invisible into visible form. My primary focus is on how both Kapoor and Nel can be seen to use their chosen materials, forms, and means of display to engage with ideas that relate to the metaphysical and allude to the intuitive and the spiritual. Their interest in Buddhist philosophy and the notion of reconciliation of opposites as well as their exploration of space and the idea of the immaterial becoming object is related to my discussion of their artworks in terms of evoking the ineffable. Kapoor's biomorphic sculptural forms covered in powder pigments, examples of his reflective stainless steel sculptures and two recent sitespecific installation artworks using smoke and water are closely examined as are examples of Nel's two-dimensional drawings using pastels, powdered earth pigments, carboniferous salts and dust and two of his site-specific installation artworks involving the use of water and refracted/reflected light. I finally discuss my own creative work in relation to the above as presented in my exhibition titled Ātmān
A dissertation submitted to the Faculty of Humanities and Social Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Masters of Arts in Fine Arts by Dissertation
Keywords: Nel, Karel (1955-); Kapoor, Anish (1954-)